The Oxford Conception Study design and recruitment experience. - Pyper, C; Bromhall, L; Dummett, S; Altman, D; Brownbill, P; Murphy, M (2006)
The Oxford Conception Study is a randomised controlled trial that aims to determine whether or not information about potential fertility from a device that monitors urinary hormones will increase the conception rate in women wishing to conceive. Three modified versions of a fertility monitor have been developed for the study. The monitor measures the levels of urinary oestrone-3-glucuronide (E3G) and luteinising hormone (LH), and the display indicates high or low fertility. The monitor requests all women to test their urine from day 6 to day 25 of the menstrual cycle inclusive. One-third of women are randomised to receive information from the fertility monitor about the early fertile time (from the first rise in E3G until the LH surge is detected), one-third receive information about the late fertile time (the onset of the LH surge and the following 2 days), and a third do not receive any information (control group). All the women are followed up for 6 months or until they are pregnant. A total of 1453 women have been recruited into the study, reaching the study recruitment goal for 80% power to detect a 10% difference in three-cycle pregnancy rate between the Late Fertile Time group (50%) and the Control group (40%), allowing for a 15% non-pregnancy drop-out rate. Follow-up of the women is currently ongoing. The primary analysis will compare the cumulative three-cycle pregnancy rate between each of the study arms. Time-specific conception probabilities will be estimated from coitus information recorded in 12-h intervals. The data from this study will also allow many additional questions to be addressed, including changes in intercourse patterns with feedback about the fertile days and other questions in relation to menstrual cycle function, sexual intercourse, stress, exposures to tobacco products, alcohol, caffeine and medications, fertility and pregnancy outcomes. In addition to presenting the study design, we review the recruitment experience for the Oxford Conception Study. We have achieved sustained and effective recruitment over time by primary use of recruiting via the Internet.